Effects of Chronic Gastritis on Sleep and Quality of Life in Adolescents - Yeliz Çağan Appak; Gonca Özyurt; Miray Karakoyun; Maşallah Baran (Journal of Pediatric Research)

(untitled)
Aim:This study aims to evaluate the sleep quality and the quality of life (QoL) of adolescents with chronic gastritis, and determine the related factors.Materials and Methods:This study included patients who were diagnosed with chronic gastritis both clinically and histopathologically. The Pittsburgh Sleep Quality Index and Epworth Sleepiness scale were used to assess sleep quality, and the Pediatric Quality of Life Inventory was used to assess QoL. The control group included healthy volunteers with no chronic diseases and no gastrointestinal system complaints.Results:Fifty-six patients with gastritis and 55 healthy volunteers were included. The patients with gastritis were found to have significantly lower overall QoL subscale, and total scale scores, except for the social functioning total score. Except for the subjective sleep quality, significant differences were seen between the groups in the sleep quality subscale, total scale, and sleepiness scale averages. The total score of the sleep quality scale was significantly higher in patients who had lower incomes than expenditure. There were no significant differences between the obese or overweight patients with gastritis and the rest of the gastritis patients in the study sample. There were no significant differences found between the Helicobacter pylori positive and negative gastritis patients in terms of the total QoL and sleepiness scale scores.Conclusion:This study is important because it is the first study in adolescents in this respect. The sleep and QoL scores of those adolescents with chronic gastritis were lower than the control group.